A new species of the hermit crab genus Ciliopagurus Forest (Crustacea: Decapoda: Anomura: Diogenidae) from southern India - Komai, Tomoyuki; Reshmi, Rema; Kumar, Appukuttan Nair Biju (Zootaxa, 2012)
The diogenid hermit crab genus Ciliopagurus Forest, 1995 is currently represented by 18 recent species, 17 species fromthe Indo-West Pacific and one species from the eastern Atlantic. In this paper, we describe a new species, Ciliopagurusgrandis, from off Kerala State, southern India. This new species is compared with six congeneric species, C. albatrossiForest, 1995, C. caparti (Forest, 1952), C. krempfi (Forest, 1952), C. liui Forest, 1995, C. macrolepis Forest, 1995, and C. shebae (Lewinsohn, 1969). It is characteristic in having weakly armed antennal acicles.